We're Going on a Leaf Hunt - Metzger, Steve; Sakamoto, Miki (New York : Scholastic Books, 2008)
Three friends go on a hike searching for fall leaves.
"Cartwheel books"
New Kids Book 2022 Summer.
AD410L
Decoding demand: 29 (low) Semantic demand: 71 (high) Syntactic demand: 30 (low) Structure demand: 54 (medium)
Keywords: Leaves -- Juvenile fiction; Autumn -- Juvenile fiction; Picture books; Fiction